PENGARUH ORGANIZATIONAL TRUST DAN EMPOWERING LEADERSHIP TERHADAP GROUP CONFLICT YANG DIMEDIASI OLEH PSYCHOLOGICAL SAFETY PADA PEGAWAI PUSKESMAS - Qurrata Aini; Wirdah Irawati (Departemen Manajemen, 2023)
This study aims to determine the influence of organizational trust and empowering leadership on group conflict mediated by psychological safety in employees of the Kuta Cot Glie Health Center, Aceh Besar District. The research method used was quantitative with a sample of 80 employees. The data collection technique used is a questionnaire. The data analysis methods used are multiple linear regression, coefficient of determination and hypothesis testing using the SPSS program. Based on the results of SPSS analysis shows that organizational trust negatively affects group conflict, empowering leadership negatively affects group conflict, Organizational Trust has a positive effect on psychological safety, empowering leadership has a positive effect on group conflict, psychological safety has a negative effect on group conflict, which means that the higher organizational trust, empowering leadership and psychological safety, the lower the occurrence of group conflict at the Kuta Cot Glie Health Center. And psychological safety can mediate the relationship between organizational trust to group conflict and also psychological safety can mediate the relationship of empowering leadership to group conflict. Penelitian ini bertujuan untuk mengetahui pengaruh organizational trust dan empowering leadership terhadap group conflict yang dimediasi oleh psychological safety pada pegawai puskesmas kuta cot glie Kabupaten Aceh Besar. Metode penelitian yang digunakan adalah kuantitatif dengan jumlah sampel 80 orang pegawai. Teknik pengumpulan data yang digunakan adalah kuesioner. Metode analisis data yang digunakan adalah regresi linear berganda, koefisien determinasi dan uji hipotesis dengan menggunakan program SPSS. Berdasarkan hasil analisis SPSS menunjukkan bahwa organizational trust berpengaruh negatif terhadap group conflict, empowering leadership berpengaruh negatif terhadap group conflict, organizational trust berpengaruh positif terhadap psychological safety, empowering leadership berpengaruh positif terhadap group conflict, psychological safety berpengaruh negatif terhadap group conflict, yang artinya bahwa semakin tinggi organizational trust, empowering leadership dan psychological safety maka semakin rendah terjadinya group conflict pada puskesmas kuta cot glie begitu juga sebaliknya. Dan psychological safety dapat memediasi hubungan antara organizational trust terhadap group conflict dan juga psychological safety dapat memediasi hubungan empowering leadership terhadap group conflict.